Supply Chain Performance: Material Flow and Financial Flow Through Supplier Relationship Management - Pudjo Sugito; Ririn Sudarwati (Business Management Research, 2026)
This study aims to analyze the direct influence of material flow and financial flow on supply chain performance, and also analyze the indirect influence through supplier relationship management on supply chain performance. This research is explorative with survey technique as data collection tool. Exogenous variables in this study are material flow and financial flow, endogenous variables are supply chain management performance and supplier relationship management as mediating variables. Material flow is the description of the transportation of raw materials, pre-fabricates, parts, components, integrated objects and final products as a flow of entities. The term applies mainly to advanced modeling of supply chain management. The indicators are inventory quantity, lead time and out of stock. The population in this study was 124 business actors with a sample of 100 business actors. The sampling technique used simple random sampling. Questionnaires as primary data collection tools, which were then analyzed with the help of Smart Partial Least Square. The results of the analysis show that there is a direct and significant influence of material and financial flow on supply chain management performance. In fact, supplier relationship management significantly mediates the influence of material flow and financial flow on supply chain management performance. Also, supplier relationship management has a significant influence on supply chain management performance. This means that both material flow, financial flow and supplier relationship management play an important role in improving supply chain management performance.